Refractive Properties of Binary Mixtures Formed by an Isomer of Chlorobutane and Butyl Ethyl Ether - Montaño, Diego F.; Artigas, Héctor; López, M. Carmen; Lafuente, Carlos (Journal of Applied Solution Chemistry and Modeling, 2014)
Refractive indices of the binary mixtures containing an isomer of chlorobutane (1-chlorobutane, 2-chlorobutane, 2-methyl-1-chloropropane, or 2-methyl-2-chloropropane) and butyl ethyl ether have been measured at seven temperatures from T = 283.15 to 313.15 K From these data refractive index deviations were calculated and correlated with a Redlich-Kister polynomial expansion. The refractive index deviations were found positive. Finally, from these refractive indices both densities and surface tensions of the studied systems were predicted and compared with previously reported values.